Clostridioides difficile infection in paediatric patients with cancer and haematopoietic stem cell transplant recipients. (August 2022) - Haeusler, Gabrielle M.; Lehrnbecher, Thomas; Agyeman, Phillip K.A.; Loves, Robyn; Castagnola, Elio; Groll, Andreas H.; van de Wetering, Marianne; Aftandilian, Catherine C.; Phillips, Bob; Chirra, Krishna M.; Schneider, Christine; Dupuis, Lee L.; et al.
Abstract: Background: Epidemiology of Clostridioides difficile infection (CDI) in paediatric cancer patients is uncertain. The primary objective was to describe the prevalence of CDI outcomes among paediatric patients receiving cancer treatments. Secondary objectives were to describe clinical features of CDI, propose a definition of severe CDI and to determine risk factors for CDI clinical outcomes. Methods: A multi-centre retrospective cohort study that included paediatric patients (1–18 years of age) receiving cancer treatments with CDI. Severe CDI definition was achieved by consensus. Univariable and multivariable regression was conducted to evaluate risk factors for CDI outcomes. Results: There were 627 eligible patients who experienced 721 CDI episodes. The prevalence of clinical cure was 82.9%, recurrence was 9.6%, global cure was 75.0% and repeated new CDI episode was 12.8%. The proposed definition of severe CDI was the presence of colitis, pneumatosis intestinalis, pseudomembranous colitis, ileus or surgery for CDI, occurring in 70 (9.7%) episodes. In univariable regression, initial oral metronidazole or initial oral vancomycin were not significantly associated with failure to achieve clinical cure or CDI recurrence. In multiple regression, oral metronidazole was significantly associated with higher odds (odds ratio (OR) 1.7, 95% confidence interval (CI) 1.0–2.7) and oral vancomycin was significantly associated with lower odds (OR 0.4, 95% CI 0.2–0.8) of repeated new episodes. Conclusion: The prevalence of clinical cure was 82.9% and recurrence was 9.6% in pediatric patients receiving cancer treatments. Severe CDI, as per our proposed definition, occurred in 9.7% episodes. Initial oral vancomycin was significantly associated with a reduction in repeated new CDI episodes. Highlights: In children with cancer and C. difficile infection (CDI), 82.9% had clinical cure. Recurrence of CDI occurred in 9.6%. A definition for severe CDI was derived and occurred in 9.7%. Oral vancomycin was significantly associated with reduced repeated CDI episodes.